BETWEEN HERE-AND-NOW AND HEREAFTER: MINDFULNESS SEBAGAI PENGAWAL ORIENTASI TERHADAP KEHIDUPAN DAN KETAKUTAN TERHADAP KEMATIAN - Yusainy, Cleoputri; Ilhamuddin, Ilhamuddin; Ramli, Amir Hasan; Semedi, Bima Pusaka; Anggono, Calvin Octavianus; Mahmudah, Maria Ulfatul; Ramadhan, Alfi Rizki (Jurnal Psikologi, 2018)
Death as an existential problem has given birth to two large spectra: fear of death or accepting it as an inevitable truth. This study aimed to examine the extent to which an individual's fear of death could be predicted by anticipation of the future (life orientation) and tendency of being here-and-now (trait mindfulness). Self-reported questionnaires of life orientation in optimism-pessimism continuum, trait mindfulness, and fear of death were presented through cloud-based online survey (N = 218 students, 73.585% females, average age 20.840 years, SD = 1.777). Hierarchical regressions analyses revealed that (i) optimistic orientation predicted a higher level of fear of death, (ii) trait mindfulness accounted for significant variance in fear of death after accounting for life orientation, and (iii) trait mindfulness did not moderate the link between life orientation and fear of death. The role of trait mindfulness was consistent in predicting lower levels of fear of death and dying of self as well as death of others, but not of dying of others. Additionally, women reported a higher level of fear of death, independent of life orientation and trait mindfulness. These individual differences should be taken into consideration when designing strategies to manage fear of death.